G.W. Barber papers - Barber, G. W. (George W.)
Correspondence, writings, reports, study data, and notes relating to Barber's work as an entomologist at the U.S. Department of Agriculture. Documents his study of the European corn borer and the corn earworm. Correspondents include F.F. Dicke and C.M. Packard.
Entomologist. Full name: George Ware Barber. Born 1890; died 1948.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English.
Keywords: Dicke, F. F. -- Correspondence; Packard, C. M. -- Correspondence; United States. -- Department of Agriculture; Corn -- Disease and pest resistance; Entomology; Insect pests; Entomologists